Design Of Flat Burr Type Coffee Bean Grinder Mill - Samuel Haposan; Saipul Bahri Daulay; Adian Rindang (Jurnal Rekayasa Pangan dan Pertanian, 2014)
Milling was done to refine food materials to be powder with a certain sieve size in order to be more easily processed into other products. The purpose of coffee beans milling was to refine the beans into coffee powder with a certain sieve size in order to be easily brewed and gives the more optimal sensation of taste and aroma. This research was aimed to design, make, and evaluate the flat burr mill type of bean grinder on robusta cofee bean. The bean quality evaluated was the effective capacity of grinder mill, lost bean persentage, and economical analysis. The results showed the effective capacity of flatt burr type grinder was 5,00 kg/hr and the lost bean persentage was 1,112%. Based on economical analysis, the cost of robusta coffee bean milling was Rp.1.074,25/kg, break even point 2.748,9 kg/year, net present value (NPV) 16% was Rp.6.147,25 ,NPV 20% was Rp.5.397.751,98, and Internal Rate of Return (IRR) was 52.81%. Keywords : Coffee, flat burr mill, grinder, rotor, stator.